Aplicación del método vivencial folklórico para mejorar el aprendizaje de la danza tradicional en los estudiantes del 5to grado de primaria de la I.E N°00654 Lucila Portocarrero Robalino de Vela - Sevillano Cadenillas, Katty Yasmín (2014)
The present investigation called application of the experiential method folk general objective has been to improve the traditional dance learning of the students in the fifth grade of primary education in the institution of education N o 00654 "Lucila Portocarrero Robalino sailing" from the town of Rioja- 2014. The problem, hypothesis, and general objective have been structured by the relationship of the variables folk experiential method and the traditional dance learning. The study is justified by its relevance and convenience, given that the proposal contributes to improve the learning of the traditional dance for students especially towards the amazonense folklore, by its social importance since it serves as a programmatic instrument of organized activities with the aim of change indifferent learning by favorable learning towards amazonense folklore, favouring human relationships; also will methodological usefulness, in effect, the results will benefit students, parents and community in general, in the sense that his sons and members of the society will be the protagonists in this improvement of the relation man - folklore; Finally he is credited with a practica! justification, that intencJs to promete artistic and cultural education, and therefore optimize the learning of traditional dance and thus raise the quality of life and promete a better cultural artistic future for children. The folkloric experiential method is systematized taking into account the theory of programming Neurolinguistics of GRINDER, j. and BANDLER, r. (1975) and the theory of the musical intelligence of GARDNER H. (2005), in addition to other theoretical contributions that served as background for the research. Based on these theories, central hypothesised in the following terms: the folkloric experiential approach will significantly improve the traditional dance learning of students in the fifth grade of primary education in the institution of education N o 00654 "Lucila Portocarrero Robalino candle." city of Rioja - 2014. xiii The sample for the study was formed by a control group and experimental group made up of two sections of fifth grade, 35 children and girls of the "A" section and 29 children and girls of the "O" section they were chosen randomly, it conducted the debugging of the intervening variables. The sample chosen, was administered a pre test to evaluate the level of learning of the traditional dance which students had prior to application of the experiential method folk then developed the three dimensions of the proposed application: education hearing, visual and kinesthetic learning sessions planned through education. After completed this period, was given the post test, both the control grqup ancJ the experimental group to determine the effect!) of the application of the experiential method folk in the experimental group. Once obtained the data, we proceeded to the analysis and respective interpretation of them, being shown that the application of the experiential method folk significantly improved the learning of traditional dance in five dimensions: internalization, rhythm, mastery of space, dress and presentation, from learning un favourable dance (average = 2.34) a learning-friendly dance (average = 36,97) in students in the fifth grade of primary education in the institution of education N o 00654 "Lucila Portocarrero Robalino of' Candle", from the town of Rioja.